Editorial - Yépez Mosquera, Belén (2024)
This issue of the Revista Ciencias Sociales tries to show a broad and varied perspective on the treatment of drugs in Latin America, emphasizing the diversity of perspectives from which they can be approached and moving away a bit from the punitive. We hope that this will contribute to the debate and analysis of a complex and very current topic in the country and the region.